EFECTO DE DOS TIPOS DE ABONOS ORGÁNICOS EN CULTIVO DE CACAO (Theobroma cacao L.) VARIEDAD CCN51 - Rivera Vera, Nicold Brigitte (2023)
The research was carried out in El Rosario Parish, Chonero, Guayas Province, Ecuador. The effect of two types of organic fertilizers (gallinaza and porquinaza) in different dosages on the cocoa crop (Theobroma cacao L.) variety CCN51: using (DBCA) with 5 treatments and a control, together with 4 replications. Maintenance pruning was carried out prior to fertilizer application, and the number of flowers, shoots, premature ear wilting and the number of healthy ears were evaluated 30 and 120 days after application.